2023
DOI: 10.1021/acsami.3c07552
|View full text |Cite
|
Sign up to set email alerts
|

Facile Functionalization of Ambipolar, Nitrogen-Doped PAHs toward Highly Efficient TADF OLED Emitters

Abstract: Despite promising optoelectronic features of Ndoped polycyclic aromatic hydrocarbons (PAHs), their use as functional materials remains underdeveloped due to their limited post-functionalization. Facing this challenge, a novel design of Ndoped PAHs with D−A−D electronic structure for thermally activated delayed fluorescence (TADF) emitters was performed. Implementing a set of auxiliary donors at the meta position of the protruding phenyl ring of quinoxaline triggers an increase in the charge-transfer property s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Organic thermally activated delayed fluorescence (TADF) materials have been extensively investigated as next-generation organic light-emitting diodes (OLEDs), which can utilize 100% of excitons by triplet-to-singlet upconversion without the need for heavy metals. 1–9 The photophysical performance of organic molecules depends highly on their excited state properties. 10–12 By designing TADF molecules with twisted donor (D) and acceptor (A) configurations, the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) can be effectively separated, leading to a reduction in the singlet–triplet energy gap (Δ E ST ) and an increase in the reverse intersystem crossing rate ( K RISC ).…”
Section: Introductionmentioning
confidence: 99%
“…Organic thermally activated delayed fluorescence (TADF) materials have been extensively investigated as next-generation organic light-emitting diodes (OLEDs), which can utilize 100% of excitons by triplet-to-singlet upconversion without the need for heavy metals. 1–9 The photophysical performance of organic molecules depends highly on their excited state properties. 10–12 By designing TADF molecules with twisted donor (D) and acceptor (A) configurations, the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) can be effectively separated, leading to a reduction in the singlet–triplet energy gap (Δ E ST ) and an increase in the reverse intersystem crossing rate ( K RISC ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Particularly, various blue luminescent materials that are capable of efficiently utilizing electrically generated triplet excitons have been developed to greatly improve the maximum external quantum efficiency (EQE max ) in blue OLEDs. 10–12 A promising method of enhancing the exciton utilization efficiency is the rational combination of the donor (D) and acceptor (A) to form the CT excitons, which favors the electron flip. 13,14 After years of endeavors, thermally-activated delayed fluorescence (TADF) and hot exciton materials, both of which possess CT characteristics and can effectively use the triplet excitons, have been successfully developed.…”
Section: Introductionmentioning
confidence: 99%
“… It has been reported that the introduction of a six-membered ring at the cove region of 1 can make the molecule positively curved to generate the bowl-shaped compound 2 , which can be further extended to generate boat-shaped compounds . When a larger seven-membered ring is placed at the cove region of 1 , the obtained molecule 3 becomes nearly planar due to the release of molecular strain by the large heptagonal ring . The π-extension at the bay region of 1 has not been studied.…”
mentioning
confidence: 99%